Diversity of Saccharomyces cerevisiae strains associated to racemes of Grillo grape variety - Alfonzo, Antonio; Francesca, Nicola; Matraxia, Michele; Craparo, Valentina; Naselli, Vincenzo; Mercurio, Vincenzo; Moschetti, Giancarlo (FEMS microbiology letters, 2020)
ABSTRACT The most important oenological characteristics of high-quality sparkling wines are high content of acidity and low pH. Racemes are late-maturing grapes of Grillo variety characterized by low pH and high content of tartaric and malic acids and, due to their intrinsic characteristics, might represent an interesting technological solution to increase acid quality of base sparkling wine. To this purpose, the use of yeasts able to ferment grape must at very low pH is mandatory for the success of the process. In this work, 261 Saccharomyces cerevisiae isolated from spontaneous vinifications of Grillo grape racemes were subject to intraspecific characterization by interdelta analysis which evidenced a total population consisting of 82 strains which were screened for their basis of technological traits including SO2 and alcohol tolerance, flocculence, growth at low temperatures and qualitative features such as H2S production. A total of 11 strains with interesting technological performance in vitro were inoculated into musts obtained from racemes of Grillo grape variety and microfermentation were monitored. For the first time an ecological investigation of yeast associated to raceme grapes has been carried out and provided an innovative strategy to improve the acidity of a Sicilian sparkling base wine from Grillo grape variety. The selection of Saccharomyces cerevisiae strains suitable for fermenting must with extremely low pH (<3) and high acidity values will improve the characteristics of the sparkling base wine.